Revisiting the Basics: Understanding Potential Demographic Differences With John Gottman's Four Horsemen and Emotional Flooding. (July 2017) - Hooper, Amy; Spann, Crystin; McCray, Tiyahri; Kimberly, Claire
It has been found that the presence of negative communicative techniques and emotional flooding in marital relationships negatively relates to marital satisfaction. However, current literature has not consistently included known demographical differences (e.g., race, gender, etc.) to truly test how these variables impact marital satisfaction. This study investigated the specific impact that both emotional flooding and negative communicative techniques had on 591 married individuals' marital satisfaction while controlling for gender, race, and length of relationship. The results indicated that emotional flooding tends to decrease as marriages go on, and refusing to talk with the partner had the greatest negative impact on relationship satisfaction regardless of demographical differences. Suggestions are provided for how therapists and practitioners can use these findings to assist couples who are using negative communication techniques and are, subsequently, experiencing marital dissatisfaction.